Volume and Area Swelling of the Polyester-Polyols - Narkhede, B.N.; Rathod, S.D.; Munde, A.S. (Asian Journal of Chemistry, 2010)
The product of partially esterifying poly (vinyl alcohol) and terephthalic acid, isophthalic acid, salicylic acid and p-hydroxy benzoic acid chlorides were polyester-polyols. Swelling of these products in water was studied. Relative and comparative studies of swelling and solubilities of polyester-polyols have been few from the determination of the density of the product before sorption and after sorption of water. Volume swelling per unit mass and volume swelling per unit volume were calculated. From the determination of the area of a square piece of the polyester-polyol before sorption and after sorption, area swelling per unit area, increase in length per unit length and increase in breadth per unit height (uncorrected for solubility) were calculated. Longitudinal swelling has also been recorded in relation to length, breadth and height. This can be related to rate of swelling in all directions.